Answer:
put 0 first
Step-by-step explanation:
Answer: 33
<u>Step-by-step explanation:</u>
The ratio of Adhy's to Ben's is 3:4 so let
Adhy = 3x
Ben = 4x
Since Ben = Adhy + 9
then 4x = 3x + 9
--> x = 9
So, Adhy = 3x = 3(9) = 27
Ben = 4x = 4(9) = 36
*************************************************************
The ratio of Ben's to Clayson's is 3:5
How do we get Ben's ratio of 3 equal to 36? <em>by multiplying by 12</em>
Ben : Clayson
<u>3 x 12</u> <u>5 x 12</u>
36 60
So, Clayson = 60
***********************************************************
The difference between Adhy and Clayson is:
Clayson - Adhy
60 - 27 = 33
Functions cannot have the same X value (the first number), but they can have the same Y value (the second number).
<span>A. {(1,2),(2,3),(3,4),(2,1),(1,0)}
B. {(2,−8),(6,4),(−3,9),(2,0),(−5,3)}
C. {(1,−3),(1,−1),(1,1),(1,3),(1,5)}
D. {(−2,5),(7,5),(−4,0),(3,1),(0,−6)}
Choice A. has two repeating X values [(1,2) and (1,0), (2,3) and (2,1)]
Choice B. has one repeating X value [(2, -8) and (2,0)]
Choice C. all has a repeating X value (1)
Choice D doesn't have any repeating X values.
In short, your answer would be choice D [</span><span>{(−2,5),(7,5),(−4,0),(3,1),(0,−6)}] because it does not have any repeating X values.</span>
Answer:
![-3\frac{1}{2}](https://tex.z-dn.net/?f=-3%5Cfrac%7B1%7D%7B2%7D%3C-3%5Cfrac%7B1%7D%7B3%7D)
Step-by-step explanation:
-3.5 means -(3 +
)
In other words, -3.5 = ![-3\frac{1}{2}](https://tex.z-dn.net/?f=-3%5Cfrac%7B1%7D%7B2%7D)
When we draw two numbers
and
on a number line,
comes first from left to right.
We know that all the numbers on a number line from left to right are in increasing order.
Therefore,
is smaller than
.
![-3\frac{1}{2}](https://tex.z-dn.net/?f=-3%5Cfrac%7B1%7D%7B2%7D%3C-3%5Cfrac%7B1%7D%7B3%7D)
Lauren is not correct.
Answer:
B.) 27ft
Step-by-step explanation:
The labeled points given: (5,18) and (1.5, 7.5)
Slope = (18 - 7.5)/(5-1.5) = 10.5 / 3.5 = 3
A linear model:
y - 18 = 3(x - 5)
y - 18 = 3x - 15
y = 3x + 3
If x = 8 seconds then the distance in feet (y) would be: (plug in x = 8 into the equation y = 3x + 3)
y = 3(8) + 3
y = 24 + 3
y = 27 ft
Answer:
B.) 27ft